Determinants of the Quality of Administrative Services - Sri Wahyuni; Connie; Asti Putri Kartiwi (Universitas Bengkulu, 2024)
The objectives of this study include describing how Reliability, Responsiveness, Assurance, Empathy, and Tangibles administrative services improve quality at SMA Negeri 10 Seluma. The research method used in this research is descriptive qualitative. The subjects in this study were principals, teachers, administrative staff, and students. This research is located at SMA Negeri 10 Seluma. Data collection techniques using interviews, observations, and document studies. The results showed Speed in responding to customer requests or need in a short time is very important for a school's administrative staff, because it will provide satisfaction to the users of its services, namely school stakeholders, Administrative staff are professional in providing academic services. Tailored to the needs of all school stakeholders, The ability of staff to be polite and friendly to customers, the ability of staff to be patient and understand customer needs and the ability of staff to give full attention to customer needs is an important part, The clothes used by administrative staff are polite and neat because of uniform scheduling at school. Suggestions were made to the school principal to continue to facilitate the development of administrative competencies.